Wind energy and economic assessment of a wind farm at Senja - Ørjavik, Ola Wang (UiT The Arctic University of Norway, 2022)
In order to deliver on the emission cuts in the Paris Agreement, additional renewable energy production is required to cover the rising energy demand. This thesis assesses the wind resources, energy production potential and the economic sustainability of a new potential wind farm, located at Senja island in northern Norway. The aim of this thesis is to decide if a new wind farm at Senja is an economic sustainable investment, based on the Levelized Cost of Electricity (LCOE) and the Net Present Value (NPV). The wind resources and the potential energy production was mapped by using a Numerical Weather Prediction (NWP) model, called Weather Research and Forecasting (WRF) model. The area of interest was chosen due to the current and future growth in energy demand at Senja. Troms Kraft has estimated that the energy consumption will increase by six times in 2030 from today’s levels. Development of a new local renewable energy plant would cover parts of this upcoming demand and increase the energy self-sufficiency at Senja. This thesis has shown that the wind farm at Senja is an economic sustainable investment, with energy production from 2030. The LCOE of the wind farm and the NPV was estimated to 39.65 øre/kWh and 55.42MNOK, respectively. This result was based on a yearly average energy production of 288.53GWh during an average weather year. This resulted in a capacity factor of 39.10%, which was higher than all the other wind farms in the vicinity of new wind farm. In the sensitivity analysis, the LCOE of the wind farm showed high sensitivity to variation in yearly energy production and initial Capital Expenditure (CAPEX).